Cell wall disassembly events in boysenberry (Rubus idaeus L. × Rubus ursinus Cham. & Schldl.) fruit development - Vicente, Ariel Roberto (2007)
Boysenberry fruit was harvested at five developmental stages, from green to purple, and changes in pectin and hemicellulose solubilisation and depolymerisation, polymer neutral sugar contents, and the activities of cell wall degrading enzymes were analysed. The high xylose to glucose ratio in the 4% KOH-soluble hemicellulose fraction suggests that xylans are abundant in the boysenberry cell wall. Although the cell wall changes associated with fruit development do not proceed in discrete stages and the cell wall disassembly is a consequence of highly regulated changes occurring in a continuum, the results suggest that the temporal changes in cell wall degradation in boysenberry account for at least three stages: an early stage (green to 75% red colour), associated with metabolism of cellulose and cross-linking glycans; an intermediate period (75 to 100% red colour), characterised by substantial pectin solubilisation without depolymerisation in which á-arabinofuranosidase increases markedly and 50% of thewall arabinose is lost; and a final stage (100% red colour to purple), characterised mainly by a reduction of pectic galactose content and a dramatic increase in pectin depolymerisation associated with higher polygalacturonase, pectin methylesterase, acetyl esterase and â-galactosidase activities. From a biotechnological perspective enzymes involved in pectin matrix disassembly seem to be the better candidates to affect boysenberry fruit late-softening by genetic intervention. A model for cell wall disassembly in boysenberry fruit is proposed.á-arabinofuranosidase increases markedly and 50% of thewall arabinose is lost; and a final stage (100% red colour to purple), characterised mainly by a reduction of pectic galactose content and a dramatic increase in pectin depolymerisation associated with higher polygalacturonase, pectin methylesterase, acetyl esterase and â-galactosidase activities. From a biotechnological perspective enzymes involved in pectin matrix disassembly seem to be the better candidates to affect boysenberry fruit late-softening by genetic intervention. A model for cell wall disassembly in boysenberry fruit is proposed.